Boruto. two blue vortex. 1 - Kishimoto, Masashi, 1974- (Shonen Jump graphic novel., 2025)
"Naruto was a young shinobi with an incorrigible knack for mischief. He achieved his dream to become the greatest ninja in his village, and now his face sits atop the Hokage monument. But this is not his story... A new generation of ninja stands in the swirling vortex of a new ninja age, with Naruto's own son, Boruto, at the center! In a cruel twist of fate, Boruto's and Kawaki's lives have been switched due to a powerful jutsu. Now branded a traitor, Boruto is on the run from his village and training with Sasuke. But when Konoha comes underattack, it's time for a grown-up Boruto to return home and show how powerful he's become!"--